2015
DOI: 10.1007/s10557-015-6571-z
|View full text |Cite
|
Sign up to set email alerts
|

ATM Protein Kinase Signaling, Type 2 Diabetes and Cardiovascular Disease

Abstract: The ataxia-telangiectasia mutated (ATM) protein kinase is well known to play a significant role in the response to double stranded DNA breaks in the nucleus. Recently, it has become apparent that ATM is also involved in a large number of cytoplasmic processes and responses, some of which may contribute to metabolic and cardiovascular complications when disrupted. Due to its involvement in these processes, therapeutic activation of ATM could potentially be a novel approach for the prevention or treatment of car… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
24
0
1

Year Published

2017
2017
2025
2025

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 38 publications
(27 citation statements)
references
References 77 publications
2
24
0
1
Order By: Relevance
“…Evidence is even less favorable that ATM haploinsufficiency strongly increases T2D risk, rejecting (for example) OR>2 at p =1.3×10 −8 . This observation could be relevant in the ongoing characterization of ATM as a potential metformin target 60–62 or if ATM activators are considered to treat cardiovascular disease 63 .…”
Section: Introductionmentioning
confidence: 92%
“…Evidence is even less favorable that ATM haploinsufficiency strongly increases T2D risk, rejecting (for example) OR>2 at p =1.3×10 −8 . This observation could be relevant in the ongoing characterization of ATM as a potential metformin target 60–62 or if ATM activators are considered to treat cardiovascular disease 63 .…”
Section: Introductionmentioning
confidence: 92%
“…These links between FA and T2D are consistent with shared pathogenetic mechanisms, first including the role(s) of OS both in T2D and in FA. It is worth noting that excess T2D prevalence is not confined to FA, as far as a number of other genetic diseases [79][80][81][82][83] display excess T2D prevalence (along with OS features), independently of their multiple and different genetic deficiencies. Thus, the co-occurrence of T2D in these disorders suggests common deficiency(ies) focused on OS/MDF abnormalities.…”
Section: Excess T2d Prevalencementioning
confidence: 99%
“…Other metabolic arenas in which ATM involvement is gaining attention are insulin response and lipoprotein metabolism, clinically represented by the metabolic syndrome. This role of ATM in cellular physiology was recently thoroughly and convincingly reviewed (Espach Y et al, 2015). Briefly, ATM was found to participate in several signaling pathways mediated by insulin (Yang DQ et al, 2000;Miles PD et al, 2007;Viniegra JG et al, 2005;Halaby MJ et al, 2008;Jeong I et al, 2010); and heterozygosity for Atm null allele in ApoEdeficient mice was found to aggravate their metabolic syndrome (Wu D et al, 2005;Schneider JG et al, 2006;Mercer JR et al, 2010), an effect that was partly relieved by the mitochondria-targeted antioxidant MitQ (Mercer JR et al, 2012.…”
Section: Functionmentioning
confidence: 99%